Practical training : organization's expectation and perception towards benefit of practical training / Herliefi Jumali and Awang Danieal Mifdhal Ag Mat Daud - Jumali, Herliefi; Ag Mat Daud, Awang Danieal Mifdhal (2016)
Practical training has been studied through many perspectives but from the organization point of view very limited source is available. The study help better understanding of what the organization want from the practical training and identify the level of the host organization expectation. This will help to better understanding what the future employer really want from their employee. The expectation can be calculated through components that have been identified. From the expectation we can see the benefit that the organizations foresee to gain from the practical training. The sample is selected through purposive technique that enables the researcher to pick the respondent that suit for their study. The finding revealed that the four component seems to have very interesting output regarding the expectation level of the organization for practical training, but the benefit that they gained shows that there are no significant difference between the department that have practical training in their organization.